Serum Copper, Iron, and Total Iron Binding Capacity in Hypothyroidism: A Case Control Study - Priyanka Thapa Manger; Gyanendra Kumar Yadav; Dhananjay Tiwari; Richa Awasthi; Durga Prasad Verma (MCBS (Molecular and Cellular Biomedical Sciences), 2023)
Background: Thyroid hormone metabolism is linked to iron metabolism. Thyroperoxidase, a key enzyme in the biosynthesis of thyroid hormones, is iron-dependent. Thus, iron deficiency might be the primary cause of hypothyroidism. Copper is another trace element that has been linked to thyroid status. Copper regulates excessive thyroxine (T4) absorption and reduces cell damage during thyroid hormone synthesis. The present study clarified the possible correlations between iron and copper levels as well as total iron binding capacity (TIBC) and triiodothyronine (T3), T4, as well as thyroid-stimulating hormone (TSH) levels in healthy and hypothyroid subjects.